Bones. The complete eleventh season [videorecording (DVD)] - Hanson, Hart (Twentieth Century Fox Home Entertainment, 2016)
Six months after Bones and Booth leave their jobs to start a new life, Booth goes missing. Desperate for distraction, Bones takes a murder case, and is devastated to learn the deceased's identity. Featuring the highly anticipated Bones and Sleepy Hollow crossover event.